Breaking the stranglehold of striga - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dipping maize seeds in a very small amount of herbicide blocks the ability of Striga hermonthica to parasitize and kill crops. Experiments over the past two years m Kenya have shown that dipping seeds in the herbicide imazapyr can triple the yield...